Crystallization Of Palm Oil-Based 9,10-Dihydroxystearic Acid Employing Isopropyl Alcohol As Solvent - Feng Ling, Gregory Koay (2007)

(untitled)
9,10-dihydroxystearic acid (DHSA) was derived from commercial grade palm oil based crude oleic acid. It was derived through the epoxidation of the unsaturation present in the oleic acid with performic acid in the presence of sulphuric acid and hydrogen peroxide, followed with in-situ hydrolysis of the epoxide with hydrogen donor such as water. DHSA promises great potential in the personal care industry. It has the prospective to act as a multipurpose intermediate in the synthesis of fine chemical products such as decorative cosmetics. However, the impurities present in DHSA could lead to skin irritation and thus the crude DHSA produced need to endure purification process in order to be qualified as an additive for the cosmetic industry. Solvent crystallization was chosen as the path in preparing DHSA crystals of at least 80% purity and of high desirability. The objective of this research was to study the effects of temperature and of solvent quality and quantity on the solvent crystallization of DHSA. On detailing the effects of temperature, four aspects were scrutinized: weight based crystal yield, particle size distribution (PSD), quality of purified DHSA crystals and crystallization operation efficiency. PSD, crystal morphology and quality of purified DHSA crystals were scrutinized when detailing the effects of solvent quality and quantity. In the course of carrying out the research work, a crystallization unit was fabricated. The detailed design and operation of the crystallization unit were described. This research, through gas chromatography (GC), PSD, Fourier Transform – Infra Red (FTIR) and scanning electron microscopy (SEM) analysis, revealed that solvent crystallization of DHSA was best carried out with the cooling temperature of 20°C, 80% isopropyl alcohol (IPA) concentration and solvent crude dihydroxystearic acid ratio of 1.0:1.0.